The Influence of Entrepreneurship Knowledge, Personality, Family Environment on Entrepreneurial Interest of Undergraduate Students Class of 2021, Faculty of Economics and Business, University of Riau - Agustina, Dio; Machasin, Machasin; Nuryanti, Nuryanti (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine 1) the influence of entrepreneurial knowledge on students' interest in entrepreneurship, 2) the influence of personality on students' interest in entrepreneurship, 3) the influence of the environment on students' interest in entrepreneurship and 4) the influence of personality, entrepreneurial knowledge and the environment on students' interest in entrepreneurship. This research is quantitative with a multiple linear regression analysis model. This research uses data obtained from distributing questionnaires to 90 respondents. The sampling method used was the simple random sampling method. This research uses statistical data analysis methods using SPSS version 25. The results of the research show that 1) Knowledge of entrepreneurship has a positive and significant effect on students' interest in entrepreneurship, 2) Personality has a positive and significant effect on students' interest in entrepreneurship, 3) Family environment has a positive and significant effect on students' interest in entrepreneurship, 4) Knowledge of entrepreneurship, personality, and The family environment together has a positive and significant effect on interest in entrepreneurship. This means that the influence of these factors interacts with each other, where individuals who have good knowledge about entrepreneurship, a strong personality, and a positive family environment will have a great interest in pursuing an entrepreneurial career.